Hundertste Reise des FFS "Anton Dohrn" nach Westgrönland (27.9. - 30.10.1966) - Bohl, H. (1967)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010